2008
DOI: 10.1016/j.bbrc.2008.08.068
|View full text |Cite
|
Sign up to set email alerts
|

Oxidative stress induced lipid accumulation via SREBP1c activation in HepG2 cells

Abstract: SREBP1c (sterol regulatory element-binding protein 1c) is a metabolic-syndrome-associated transcription factor that controls fatty acid biosynthesis under glucose/insulin stimulation. Oxidative stress increases lipid accumulation, which promotes the generation of reactive oxygen species (ROS). However, we know little about the role of oxidative stress in fatty acid biosynthesis. To clarify the action of oxidative stress in lipid accumulation via SREBP1c, we examined SREBP1c activity in H2O2-treated mammalian c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

6
98
1
2

Year Published

2009
2009
2021
2021

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 153 publications
(107 citation statements)
references
References 25 publications
6
98
1
2
Order By: Relevance
“…4). Furthermore, we and other groups previously revealed that ROS promote lipid accumulation by stimulating SREBP-1c activity (Kohjima et al 2007;Sekiya et al 2008). These findings suggest that the anti-oxidative activity of YGS may have led to the suppression of SREBP-1c transcriptional activity.…”
Section: Discussionsupporting
confidence: 63%
See 1 more Smart Citation
“…4). Furthermore, we and other groups previously revealed that ROS promote lipid accumulation by stimulating SREBP-1c activity (Kohjima et al 2007;Sekiya et al 2008). These findings suggest that the anti-oxidative activity of YGS may have led to the suppression of SREBP-1c transcriptional activity.…”
Section: Discussionsupporting
confidence: 63%
“…In patients with lipid metabolic disorder, Reactive Oxygen Species (ROS) level in the blood is a little higher than normal people (Mecocci et al 2002;Potenza et al 2009). We have reported that ROS promotes lipid accumulation through the activation of SREBP-1c (Sekiya et al 2008). Therefore, we focused on SREBP-1c as a key factor for understanding the mechanism of lipid metabolic disease.…”
mentioning
confidence: 99%
“…It is known that SREBP is activated by Akt, and it regulates the expression of cholesterol and fatty acid synthetic enzymes (Hua et al 1993). We also showed that ROSs induce SREBP1c transcriptional activity (Sekiya et al 2008). These findings indicate that the antioxidant effect of EGCG possibly reduces the transcriptional activity of SREBP1c.…”
Section: Discussionsupporting
confidence: 60%
“…In addition, activated SREBP also promotes the expression of glucose and fatty acid synthesis enzymes. We also revealed the fact that ROSs accelerate SREBP1c transcriptional activity (Sekiya et al 2008). …”
Section: Introductionmentioning
confidence: 71%
“…A transcriptome study of the acute phase response to LPS in vivo reported a coordinate decrease of cholesterogenic gene expression (100). On the other hand, oxidative stress increased lipid hepatic lipogenesis by stimulating LXR␣ and SREBP-1c in HepG2 cells (101,102). Moreover, in livers of glutathione-deficient rats, lower mRNA abundance of SREBP-1c was detected (103), whereas in enterocytes, TNF␣ treatment induced MTP protein and SREBP-1c protein and mRNA levels (104).…”
Section: Discussionmentioning
confidence: 99%